Trends in postgraduate education of doctors in oncology in Poland in 2010-2020 in the face of demographic and epidemiological challenges - Kocik, Janusz; Moczydłowska, Marta; Mazurek, Magdalena; Zgliczyński, Wojciech Stefan; Pinkas, Jarosław; Religioni, Urszula; Pruszyński, Jacek; Ostrowski, Janusz; Grudziąż-Sękowska, Justyna (Wiedza Medyczna, 2022)
Introduction: The system of specialization training in oncology is subject to constant shifts in response to the changing health needs in Poland. Both the specialization programs and the training mode have evolved, and the system’s ability to train more specialists has increased. Epidemiological trends in cancer diseases indicate a further increase in the incidence and mortality. Moreover, the advancement at diagnosis is likely to be higher in the coming years due to neglect during the COVID-19 pandemic. Treatment of advanced neoplasms will require the availability of more specialists in oncological disciplines, especially conservative ones, as well as specialists supporting oncological care. Aim of the study: The study aimed to determine the quantitative changes taking place in the system of specialist education of doctors in oncological fields between 2010 and 2020 and to assess the trends of changes in relation to the growing demand and challenges of the pandemic. Material and methods: The material for the analysis was the data of the register of doctors undergoing specialization training conducted by the Centre of Postgraduate Medical Education of Warsaw in 2010-2020. The material analysis was quantitative. Results: The conducted analysis shows the constant development of specialization education in the fields of oncology in 2010-2020, aimed at covering the demand for specialists in the studied fields. The pace of growth may prove insufficient in the long term in view of the aging of the population and the associated increasing incidence and prevalence of neoplastic diseases. Worryingly, the newly formed specialists will have to deal in the near term with the post-pandemic wave of patients with advanced cancers who require more frequent treatment combined with careful palliative care during and after treatment. Detailed results are presented in Tables 1-7 and 8 in the Annex. Conclusions: The conducted analysis shows the constant development of specialization education in the fields of oncology in the years 2010-2020, aimed at covering the demand for specialists in the studied fields.